Relationship Between Stress Levels With Dementia Among Pre-Elderly In Sukomanunggal District Surabaya City - Adelia, Vikky; Aulia, Salma Shafrina (Jurnal Gizi dan Kesehatan Nusantara, 2025)
Dementia is a clinical syndrome characterized by a decline in cognitive function that can affect memory, language, attention, and other thinking abilities to interfere with daily activities. This study aims to analyze the relationship between stress levels and the incidence of dementia in pre-elderly people in Sukomanunggal District, Surabaya City. The study used a cross-sectional approach with a purposive sampling technique and obtained a sample of 70 pre-elderly respondents (aged 45-59 years) in Sukomanunggal District, Surabaya City. Stress levels were measured using the Perceived Stress Scale (PSS)-10 and dementia screening using the Mini-Mental State Examination (MMSE). Data analysis used the Spearman Rank Test. The results showed a significant relationship between stress levels (p = 0.044; r = 0.242) and dementia in pre-elderly people in Sukomanunggal District, Surabaya City. The research subjects had moderate stress levels and did not experience dementia (normal). The results of this study are expected to provide an overview of the role of stress on the risk of dementia in the pre-elderly age group, so that it can be the basis for developing prevention strategies and early intervention to minimize the risk of dementia.